What not to do in acute otitis media: the top five recommendations proposed by the Italian Society of Preventive and Social Pediatrics. Issue 10 (3rd October 2017) - Chiappini, Elena; Bortone, Barbara; Doria, Mattia; Landi, Massimo; Di Mauro, Giuseppe; Marchisio, Paola
ABSTRACT: Introduction : With the aim to reduce inappropriate procedures and antibiotic therapy in the management of acute otitis media (AOM) in children, the Italian Society of Preventive and Social Pediatrics (SIPPS) proposed a top five list of recommendations for clinical practice. Areas covered : AOM is one of the most frequent reasons for antibiotic prescription in pediatric age. The over-estimation of AOM is associated with inappropriate treatment, increased costs, adverse events and spread of antibiotic resistance. Thus, the most recent guidelines provided stringent diagnostic criteria and considered the 'watchful waiting' approach, limiting the immediate antibiotic therapy to a well-characterized subgroup of children. Expert commentary : The five recommendations proposed are: 1) Do not diagnose AOM without having documented the presence of middle ear effusion 2) Do not diagnose AOM without examining the entire tympanic membrane; 3) Do not treat immediately all cases of AOM with antibiotics; 4) Do not administer ear analgesic drops until examining the whole tympanic membrane 5) Do not use macrolides in the AOM therapy. This list of top five recommendations could be a novel tool to spread the key messages on the guidelines and to promote the correct diagnostic procedures as well as a rational use of antibiotics in children.